PENGARUH KESIAPAN UNTUK BERUBAH DAN PROACTIVE BEHAVIOR TERHADAP KINERJA - Kustini, Kustini; Izaak, Wilma Cordelia; Rini, Hesty Prima (BISMA: Jurnal Bisnis dan Manajemen, 2020)
This study aims to analyze the effect of readiness to change on employee performance through proactive behaviour. The readiness to change will lead to proactive behaviour in implementing the Financial Budget System (SIGARKU), which will impact employee performance. This study used the census sampling technique. The sample consisted of 80 lecturers and education staff of UPN "Veteran" East Java as the SIGARKU implementers. Data were analyzed using Structural Equation Modeling with Partial Least Square approach. Results of this study indicate that readiness to change has a direct effect on performance. Readiness to change has a positive effect on proactive behaviour, and proactive behaviour positively affects performance. However, proactive behaviour does not mediate the effect of readiness to change on performance. Keywords: performance, proactive behaviour, readiness to change, SIGARKU